U-series isotope constraints on the rates of aeolian-impacted basaltic weathering under tropical climate - Ming, Guodong; Huang, Jingyi; Sheng, Jiaru; Gong, Yingzeng; Guo, Jiye; Yu, Huimin; Cheng, Wenhan; Lundstrom, Craig C.; Huang, Fang (Global and planetary change, 2025)
The chemical weathering of basalt rocks is crucial for stabilizing Earth's habitability and carbon cycle. Currently, the soil chemistry and weathering rates of basalt under significant aeolian influence are not fully understood. This study addresses this gap by investigating the U geochemistry and regolith production rates in a highly weathered basalt profile in Southern China. The εNd(0) values decrease from the bedrock sample (4.68) to the top soils (0.94), indicating aerosol input from the top. Dust accretion decrease downward and significantly affects the vertical distribution of U (R2 = 0.86), while the chemical mobilization of U is controlled by binding with Fe oxides-organic matter complexes (R2 = 0.33). The influence of dust accretion diminishes to insignificant (less than 9 % for U amount) below 330 cm, meeting the model's criteria for estimating U-series isotope-based regolith production rates. The estimated regolith production rates for depths of 445 cm, 370 cm, and 330 cm are ∼ 10 m/Myr, ∼ 5.5 m/Myr, and ∼ 3 m/Myr, respectively. These rates decrease with increasing depth, illustrating the depletion of soluble materials as the weathering profile thickens. CO2 consumption fluxes calculated from soil chemistry (< 193 × 103 mol/km2/yr) are lower than those from river chemistry. Regolith development in the Leizhou Peninsula may account for < 25 % of total chemical erosion, suggesting significant hidden erosion processes. These observations indicate that other potential weathering sources in aquifers and steeper terrains should be independently estimated when assessing basin-scale CO2 consumption. •Aeolian impacted basaltic weathering in tropical climate and its rates are studied.•U distribution is governed by dust mixing and iron-organic complexes.•The δ238U of the regolith aligning with that of the bedrock due to “rind effect”.•Regolith production rates decline with decreasing depth as the regolith thickens.•Regolith contributes <25 % of total chemical erosion, revealing hidden processes.